Cross Sectional Study and Risk Factors Analysis of Francisella tularensis in Soil Samples in Punjab Province of Pakistan - Muhammad, Javed; Rabbani, Masood; Shabbir, Muhammad Zubair; Muhammad, Khushi; Ghori, Muhammad Taslim; Chaudhry, Haroon Rashid; Ul Hassnain, Zia; Jamil, Tariq; Abbas, Tariq; Chaudhry, Muhammad Hamid; Haisem-ur-Rasool, Muhammad; Ali, Muhammad Asad; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Tularemia is an endemic zoonotic disease in many parts of the world including Asia. A cross-sectional study was conducted to determine genome-based prevalence of Francisella tularensis (Ft) in soil, assess an association between its occurrence in soil and likely predictors i.e. macro and micro-nutrients and several categorical variables, and determine seroconversion in small and large ruminants. The study included a total of 2280 soil samples representing 456 villages in eight districts of the Punjab Province of Pakistan followed by an analysis of serum antibodies in 707 ruminants. The genome of Ft was detected in 3.25% (n = 74, 95% CI: 2.60 – 4.06) of soil samples. Soluble salts (OR: 1.276, 95% CI: 1.043-1.562, p =0.015), Ni (OR: 2.910, 95%CI: 0.795-10.644, p=0.106), Mn (OR: .733, 95% CI: .565-.951, p =0.019), Zn (OR: 4.922, 95% CI:.929-26.064, p =0.061) and nutrients clustered together as PC-1 (OR: 4.76, 95% CI: 2.37-9.54, p =0.000) and PC-3 (OR: 0.357, 95% CI: 0.640, p =0.001) were found to have a positive association for the presence of Ft in soil. The odds of occurrence of Ft DNA in soil were higher at locations close to a water source, including canals, streams or drains, [χ2 = 6.7, OR = 1.19, 95% CI:1.05-3.09, p = 0.004] as well as places where animals were present [χ2 = 4.09, OR = 2.06, 95% CI: 1.05-4.05, p=0.02]. The seroconversion was detected in 6.22% (n=44, 95% CI: 4.67 – 8.25) of domestic animals. An occurrence of Ft over a wide geographical region indicates its expansion to enzootic range, and demonstrates the need for further investigation among potential disease reservoirs and at-risk populations, such as farmers and veterinarians.